Phytochemical content, antioxidant activities and androgenic properties of four South African medicinal plants - Nelisiwe Prenate Masuku; Jeremiah Oshiomame Unuofin; Sogolo Lucky Lebelo (Shahrekord University of Medical Sciences, 2020)
Introduction: This study aimed to investigate the phytochemical contents, antioxidant activities, and androgenic properties of Peltophorum africanum Sond, Trichilia emetica Vahl, Terminalia sambesiaca, and Ximenia caffra. Methods: The finely powdered leaves of the selected plants were extracted using acetone, aqueous, and methanol as solvents. The total phenolics and flavonoids contents were determined from gallic acid and quercetin standard curves. The antioxidant activities of these extracts were evaluated using 1, 1-Diphenyl-2-picrylhydrazyl ( DPPH) assay. The effect of plant extracts (100-1000 µg/mL) on TM3 Leydig cells was assessed using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay. Testosterone levels were measured using ELISA kit. Results: The methanol extracts of T. sambesiaca and X. caffra revealed higher total phenolic and flavonoid contents (102.13±2.32 mg/g GAE and 1.05±0.04 mg/g QE, respectively) than other plant extracts. The acetone and methanol extracts of P. africanum revealed the best IC50 value (12.50 ± 0.052 µg/mL) against DPPH than the other plant extracts and ascorbic acid. The MTT assay results showed that all varying concentrations of plant extracts maintained cell viability and were not cytotoxic with IC50 values of greater than 20 µg/mL. The methanol extract of T. sambesiaca had the highest testosterone production at 500 µg/mL (0.399 ng/mL) when compared with the basal control while at the concentration of 500 µg/mL the acetone extracts of P. africanum and T. sambesiaca had significantly high testosterone production 0.147 and 0.188 ng/mL respectively when compared with basal control. Conclusion: The results reveal that these plants possess antioxidants and androgenic property and suggest the potential use for the treatment of male infertility.